Immune evaluation of granulocyte-macrophage colony stimulating factor loaded hierarchically 3D nanofiber scaffolds in a humanized mice model - Chen, Rui; Li, Yujie; Zhuang, Yangyang; Zhang, Yiming; Wu, Hailong; Lin, Tao; Chen, Shixuan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Immune evaluation of biomaterials for tissue regeneration is a critical preclinical evaluation. The current evaluation criterion (ISO 10993-1 or GB/T 16886) uses rodents to perform the immune evaluation. However, the immune system of rodents is different from humans, the obtained results may not be reliable, which could lead directly to the failure of clinical trials. Granulocyte-macrophage colony-stimulating factor (GM-CSF) shows a great potential application in tissue regeneration by regulating local immune responses. The presented work combines the advantages of GM-CSF (immunoregulation) and hierarchically 3D nanofiber scaffolds (tissue regeneration). Methods: Firstly, we fabricated GM-CSF loaded 3D radially aligned nanofiber scaffolds, and then subcutaneous implantation was performed in humanized mice. The whole scaffold and surrounding tissue were harvested at each indicated time point. Finally, the cell infiltration and local immune responses were detected by histological observations, including H&E and Masson staining and immunochemistry. Results: We found significant cell migration and extracellular matrix deposition within the 3D radially aligned nanofiber scaffold after subcutaneous implantation. The locally released GM-CSF could accelerate the expression of human dendritic cells (CD11c) only 3 days after subcutaneous implantation. Moreover, higher expression of human cytotoxic T cells (CD3+/CD8+), M1 macrophages (CD68/CCR7) was detected within GM-CSF loaded radially aligned nanofiber scaffolds and their surrounding tissues. Conclusions: The 3D radially aligned scaffold can accelerate cell migration from surrounding tissues to regenerate the wound area. And the locally released GM-CSF enhances dendritic cell recruitment and activation of cytotoxic T cells and M1 macrophages. Taken together, the GM-CSF loaded 3D radially aligned nanofiber scaffolds have a promising potential for achieving tissue regeneration.